(3GdLGfH GdeXde aj MjGI GdYeds - (3YGeQ Ydj MSjf(B, (3GdYWhjs ((3GdYQGb(B:s (3eDSSI OGQ GdUGOb GdKbGajI(B,s, 2023)
(3ebOeI aj ShA GdSdhc GdJfXjej, GdSdhc GdJfXjej ebGHd ShA GdSdhc GdJfXjej , fHPI JGQjNjI, eaghe ShA GdSdhc GdJfXjej , deGPG fOQS ShA GdSdhc GdJfXjej , JHhjH CTcGd ShA GdSdhc GdJfXjej, EOGQI ShA GdSdhc GdJfXjej, Sdhc GdYed GdefMQa, eagheg, CHYGOg, YhGbHg hGdJcGdja GdfGLeI Yfg, CSHGH Sdhc GdYed GdefMQa, GdJSjjS GdJfXjej, eagheg, CHYGOg, eSHHGJ GdJSjjS GdJfXjej hYhGbHg aj ecGf GdYed, GdETQGa GdeJYSa, GdETQGa GdeJYSa habG dfXQjI GdYOGdI GdJfXjejI, GdETQGa GdeJYSa habG dfXQjI GdJHGOd GdELJeGYj, GdETQGa GdeJYSa habG dfXQjI GdYRh, fehPL GdETQGa GdeJYSa, CSHGHg, YhGbHg, GdJbhjV GdELJeGYj aj ecGf GdYed, GdJfeQ aj ecGf GdYed, GdUQGY GdJfXjej, GdebGWYI aj ecGf GdYed, GdJgce GdJfXjej, GdJScY GdGLJeGYj aj ecGf GdYed, GdJZjH Yf GdYed(B.s
(3GdeQGLY U(B.279s
Keywords: (3BOGH GdSdhc s; (3GdSdhcs; (3GdSdhc GdELJeGYjs; (3GdSdhc GdEOGQjs; (3GdSdhc(B- (3GfMQGas; (3GdYed hGdYeGds